Effects of 1kg overload use in physical fitness in middle-aged and elderly women - doi: 10.4025/reveducfis.v22i3.10348 - Silva, Juliana Rafaela Andrade da (2011)
The objective of this study was to analyze the effects of 1 kg of overload in a community-based exercise program in physical fitness in older and middle-aged women. Twenty-one middle aged and elderly women were randomly divided into two groups: workload (WG n=12) and control (CG n=9). Both groups performed 16 sessions of the same exercise program, however, the WG performed the exercises with 1kg of overload. Before and after the training program both groups performed fitness test battery. After the training program the improvements in 30-s chair stand, arm curl, 2-min step test, 8-ft up-and-go, chair sit-and-reach, back scratch were similar between groups. In conclusion, the inclusion of a 1kg overload did not promote further increases in physical fitness in older and middle-age women.